Apparent total tract digestibility, ruminal fermentation, and blood metabolites in beef steers fed green-chopped cool-season forages. (4th June 2020) - Schulmeister, Tessa M; Ruiz-Moreno, Martin; Garcia-Ascolani, Mariana E; Ciriaco, Francine M; Henry, Darren D; Benitez, Jefferson; Santos, Erick R S; Dubeux, Jose C B; Lamb, Graham C; DiLorenzo, Nicolas
Abstract: An experiment was conducted during the winter of two consecutive years to evaluate the effects of feeding green-chopped cool-season forages on digestibility, ruminal fermentation, and blood parameters in beef steers. Nine ruminally cannulated Angus crossbred steers (year 1: 359 ± 79 kg; year 2: 481 ± 105 kg) received ad libitum green-chopped forages from pastures planted with one of the following mixtures: 1) OAT = Horizon 201 oats ( Avena sativa L.)/Prine annual ryegrass ( Lolium multiflorum Lam.) at 95 and 17 kg/ha, respectively; 2) RYE = FL401 cereal rye ( Secale cereale L.)/Prine annual ryegrass ( Lolium multiflorum Lam.) at 78 and 17 kg/ha, respectively; or 3) TRIT = Trical 342 triticale ( X Triticosecale spp.)/Prine annual ryegrass ( Lolium multiflorum Lam.) at 95 and 17 kg/ha, respectively. Intake was measured using the GrowSafe system and orts were discarded prior to subsequent feeding. After a 14-d adaptation, feed and fecal samples were collected twice daily for 4 d to determine apparent total tract nutrient digestibility using indigestible neutral detergent fiber (NDF ) as an internal marker. On day 19, blood and ruminal fluid samples were collected every 3 h during a 24-h period to analyze plasma urea nitrogen (PUN ) and glucose, ruminal pH, and concentration of ruminal ammonia nitrogen (NH3 -N) and volatile fatty acids (VFA ). Data were analyzed as a generalized randomized block design with repeated measures using the PROC MIX of SAS. No effect of treatment ( P > 0.05) was observed for intake of dry matter, organic matter (OM ), crude protein, NDF, or acid detergent fiber. Apparent total tract digestibility of nutrients was greater ( P < 0.05) for OAT and TRIT when compared with RYE, with OM digestibility being 82.7%, 79.6%, and 69.5%, respectively. An effect of time ( P < 0.01) was observed for ruminal pH. Plasma concentration of glucose was greater ( P < 0.01) in steers consuming OAT, whereas steers fed RYE had greater ( P < 0.05) concentrations of ruminal NH3 -N and PUN, and the least concentration of total ruminal VFA ( P < 0.05), despite having the greatest ( P > 0.05) molar proportion of acetate, branched-chain VFA, and acetate:propionate. Increased nutrient digestibility and favorable ruminal fermentation and blood metabolites of OAT and TRIT are potentially conducive to enhanced growth performance when compared with RYE.